Pengembangan Media Pembelajaran Kotak Pintar pada Materi Sikapku Peduli Lingkungan Siswa - Putri, Shidqoh Rahmawati; Pramesti, Diana; Afrianto, Gatot (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2025)
Pancasila Education learning currently still centers on learning media such as images and books, making it difficult for students to understand the material. The purpose of this study is to develop smart box learning media for elementary school students that is valid, practical, and effective. The type of research used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), with the research subjects being 27 second-grade students from UPTD SD N 21 Mendobarat. The data collection techniques and instruments used were observation, interviews, questionnaires, and tests. The data analysis technique was descriptive quantitative, with validity data obtained from one media expert and one content expert, practicality from the results of the respondents' questionnaire analysis, and effectiveness from the analysis of pre-test and post-test scores. Based on the assessment results conducted by media validators, it was found that 94% (Very Valid) and material validators 80% (Valid). The results of the student response questionnaire for small group trials were 98% (Very Practical), large group trials 98.6% (Very Practical), and class II teacher responses 100% (Very Practical). The N-Gain test result was 0.7273 > 0.7 (High) with a percentage value of 72.7273 or equivalent to 72% (Effective), so the smart box learning media is considered effective in improving student learning outcomes. Meanwhile, the One-Sample t-test results showed a sig (2-tailed) value of 0.000 < 0.05 (Ha accepted), indicating a significant difference between the average student understanding before and after using the smart box learning media compared to the previously determined value.